Functional and immunochemical characterization of advanced glycation end-product (AGE)-modified low-density lipoproteins (AGE-LDL). - Rahimkhani, Shermin. (University of Ottawa (Canada), 2000)
Low-density lipoproteins (LDL), the major cholesterol carriers of human plasma contain a single copy of apolipoprotein B (apoB). As a ligand for the cell surface LDL receptor, apoB has an important role in cholesterol metabolism. Biochemical modification of apoB, such as modification with advanced glycation end-products (AGEs) can dramatically affect the functional integrity of LDL. Diabetic or renally impaired patients exhibit elevated concentrations of AGE-modified LDL (AGE-LDL). A dyslipidemia characterized by hypertriglyceridemia, increased levels of small-dense LDL, and low plasma concentration of HDL occurs commonly in such patients and future coronary artery disease risk is increased 2 to 5 fold. The objective of this study was first to provide a more precise molecular basis for the reduced LDL receptor-binding activities of AGE-LDL, and then to compare the structural and functional properties of LDL that have experimentally been AGE-modified in vitro with LDL modified in vivo under pathophysiological conditions of diabetes or renal insufficiency. (Abstract shortened by UMI.)
Keywords: Chemistry, Biochemistry.